Le Musée imaginaire : de Malraux à Gary - Grimalt, Esther (Literatūra, 2022)
The concept of an imaginary museum developed by André Malraux in the eponymous book was taken up by Gary, notably in his novel La Danse de Genghis Cohn. This reappropriation of the concept allows to reborn it in a more subversive form and to pose the question of the aestheticization of suffering through art. In doing so, Gary, while paying tribute to the writer and intellectual who was one of the first to believe in him, allows himself to extend his reflection on the concept of imaginary museum, thus linking their two thoughts that seem to respond to each other like mirrors placed face to face in his work.
Keywords: Romain Gary; André Malraux; Musée imaginaire; La Danse de Gengis Cohn; art; esthétisation de la souffrance; intertextualité